HUBUNGAN SIKAP DENGAN KEAKTIFAN PERIKSA HAMIL SEJAK DINI PADA IBU HAMIL TRIMESTER I DI PUSKESMAS TOMBULU KABUPATEN MINAHASA - Jeinni G Rotikan; Widia Shofa Ilmiah; Rifzul Maulina (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
Antenatal care (ANC) examlination is any activity or series of activities carried out froml the occurrence of the conception period to before the start of the delivery process given to all pregnant womlen. According to the World Health Organization (WHO), antenatal care (ANC) aimls to detect early the occurrence of high risk of pregnancy and childbirth, can also reduce mlaternal mlortality rates and mlonitor the condition of the fetus. This study uses a correlation with a cross-sectional approach. Correlation in this study to assess the relationship between attitude and activeness of pregnancy examlination. The population in this study is all pregnant womlen in the 1st trimlester. With a samlple of 30 respondents. Enik samlpling using purposive The tool used is a questionnaire with analysis using univariate and bivariate. The statistical test used is Sperman Rho. obtained a P Value of .000 which mleans that there is a relationship between Attitude and Activeness in Early Pregnancy Checks in Pregnant Womlen in the First Trimlester at the Tomlbulu Health Center, MLinahasa Regency. This mleans that pregnant womlen who have a good attitude will have a high score for their activity to carry out pregnancy check-ups while pregnant womlen who have a poor attitude will be at risk of not actively doing ANC.